PENGARUH MODEL PEMBELAJARAN PBL MENGGUNAKAN MEDIA AUDIO VISUAL TERHADAP MINAT DAN HASIL BELAJAR BIOLOGI - Herlina, Mety; Syahfitri, Jayanti; Oktariani, Yeni (Jurnal BIOEDUIN, 2020)
This research was conducted in 2019 which is a quasi-experimental study with a sample of experimental class and control class taken through random sampling. Data collected through a questionnaire to see interest and test instruments to see student learning outcomes. Based on the research, the interest and learning outcomes of the experimental class students were higher than the control class. This is seen from the average value of learning interest in the experimental class 69.62 and the average learning outcomes (post-test) 77.59 while the average learning interest in the control class is 50.48 and the average learning outcomes (post-test) 71, 6 After the t-test obtained from the interest in student learning outcomes obtained significant 0,000 meaning <0.005 and obtained Tcount 5.393 and Ttable 2.007 then 5.393> 2.007, it can be concluded that there is an influence of learning interest in the experimental class and the control class. While the t-test of learning outcomes (posttest) obtained significance of 0,000 meaning <0.05 and obtained Tcount 3,948 and Ttable 2,647 then 3,948> 2,647. Based on these findings it can be concluded that the PBL model using audio visual media influences student interest and learning outcomes. . Penelitian ini telah dilakukan pada tahun 2019 yang merupakan penelitian quasi experiment dengan sampel kelas eksperimen dan kelas kontrol yang diambil melalui random sampling. Data yang dikumpulkan melalui instrument angket untuk melihat minat dan instrument tes untuk melihat hasil belajar siswa. Berdasarkan penelitian diperoleh minat dan hasil belajar siswa kelas eksperimen lebih tinggi dari kelas kontrol. Hal ini dilihat dari nilai rata-rata minat belajar kelas eksperimen 69,62 dan rata-rata hasil belajar (postest) 77,59 sedangkan rata-rata minat belajar pada kelas kontrol 50,48 dan rata-rata hasil belajar (postest) 71,6. Setelah dilakukan uji-t yang diperoleh dari minat hasil belajar siswa yang diperoleh signifikannya 0,000 artinya < 0,005 dan diperoleh Thitung 5,393 dan Ttabel 2,007 maka 5,393> 2,007 maka dapat disimpulkan terdapat pengaruh minat belajar pada kelas eksperimen dan kelas kontrol. Sedangkan uji-t hasil belajar (postest) diperoleh signifikanya 0,000 artinya < 0,05 dan diperoleh Thitung 3,948 dan Ttabel 2,647 maka 3,948 > 2,647. Berdasarkan temuan ini dapat disimpulkan bahwa model PBL menggunakan media audio visual berpengaruh terhadap minat dan hasil belajar siswa.